PENGARUH LIKUIDITAS DAN ARUS KAS TERHADAPLABA PT ANEKA TAMBANG DI BURSA EFEKINDONESIA (STIE Rajawali Purworejo, 2018)
The purpose of this research is to know the effect of liquidity and cash flow to earnings at PT Aneka Tambang In Indonesia Stock Exchange. Data collection using qualitative and quantitative methods. This research uses data analysis method, multiple regression, coefficient determination T test and F test. Based on the research that the authors do finally obtained the regression equation Y = (2.016) + 0.229X1-0.720X2. This means that if the value of the liquidity variable and the cash flows of the study are equal to zero, then the level ormagnitude of the profit variable will be (2.016), while angkadeterminasi is btained by 0.401 or 40.1% and the rest59.9% is influenced by other factors which was not investigated in this study. Partially there is no positive and significant influence between liquidity and cash flow to earnings. And simultaneously there is no positive and significant influence between variable liquidity and cash flow to earnings.